Permeability-controllable SERS biosensor based on enzymatic degradable multilayered polyelectrolyte film - Loh, Jia Wen (2015)
A permeability-controllable SERS-based sensing strategy is developed by utilizing the layer-by-layer thin film fabrication on silver nanoflower-modified substrate. SERS intensity variation can be used to indicate the change of permeability level of the multilayered polyelectrolyte film (MPF) due to the enzymatic degradation reaction of the layers. The enzymatic degradation reaction of the polyelectrolyte multilayers leads to film deconstruction and hence allowing higher penetration of adsorbed molecules to contact with substrate. Consequently, SERS enhancement could occur, leading to higher SERS signal intensity for various applications especially biosensing. The SERS intensity decreases when the number of layer coating on the substrate is higher in both enzymatic and non-enzymatic conditions. However, we hypothesized that enzyme trypsin with certain threshold concentration is able to recover the SERS intensity of substrate which initially inhibited by multilayered films. It was observed that the intensity recovery is higher with the use of higher enzyme concentration, indicating higher layer degradation rate. Furthermore, different laser wavelength excited by Raman imaging instrument is studied to determine its feasibility in the detection of SERS enhancement induced by the hotspots at the junctions of “flower-like” silver nanostructures.